Zero tolerance for genital mutilation: a review of moral justifications - Earp, BD (Springer, 2020)
Purpose of Review To summarize and critically evaluate the moral principles invoked in support of zero tolerance laws and policies for medically unnecessary female genital cutting (FGC).